New product introduction by incumbent firms - Siebert, Ralph (online, 1999)
Abstract:
urn:nbn:de:0168-ssoar-194759
Keywords: (stw)Innovationswettbewerb; (stw)Innovation; (stw)Markteintritt; (stw)Duopol; (stw)Produktqualität; (stw)Wettbewerb; (stw)Theorie; (thesoz)Produkt; (thesoz)ökonomisches Modell; (thesoz)Marktform; (thesoz)Innovation; (thesoz)Markterschließung; (thesoz)Unternehmenspolitik; (thesoz)Kosten; (thesoz)Produktpolitik; (thesoz)Produktion; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Innovationswettbewerb; Innovation; Markteintrittsstrategie; Dyopol; Qualität; Wettbewerb; Theorie